2014
DOI: 10.9738/intsurg-d-13-00059
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mortality of Anastomotic Dehiscence Requiring Reoperation After Rectal Carcinoma Resection

Abstract: Anastomotic dehiscence (AD) requiring reoperation is the most severe complication following anterior rectal resection. We performed a systematic review on studies that describe AD requiring reoperation and its subsequent mortality after anterior resection for rectal carcinoma. A systematic search was performed on published literature. Data on the definition and rate of AD, the number of ADs requiring reoperation, the mortality caused by AD, and the overall postoperative mortality were pooled and analyzed. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…AL is a clinical problem because it may cause acute peritonitis and pelvic sepsis. It may also have an adverse effect on long‐term bowel function, quality of life, cancer‐specific survival, local recurrence and rate of permanent stoma. Previous studies reported that the incidence of major AL was reduced when CJP reconstruction was performed in patients with a stapled colorectal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AL is a clinical problem because it may cause acute peritonitis and pelvic sepsis. It may also have an adverse effect on long‐term bowel function, quality of life, cancer‐specific survival, local recurrence and rate of permanent stoma. Previous studies reported that the incidence of major AL was reduced when CJP reconstruction was performed in patients with a stapled colorectal anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical AL has a negative impact on postoperative mortality, risk of permanent stoma, bowel function and quality of life. All this considered, the authors hypothesized that CJP reconstruction after LAR for rectal cancer may reduce the incidence of AL compared with the standard SCRA, and may improve bowel function and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…AL is a burden on valuable healthcare resources; the average cost of AL following AR is £17 220 [39]. It is one of the leading causes of death following rectal cancer surgery, with around 20-30% of all 30-day mortality being directly attributed to AL [7,8]. In O232 Intra-operative fluorescence angiography to prevent anastomotic leak those patients who survive AL, it is a cause of long-term morbidity, associated with poor bowel function, reduced QoL, increased risk of cancer recurrence and high rates of permanent stoma [5,6,9,40].…”
Section: Discussionmentioning
confidence: 99%
“…It increases postoperative morbidity from~20% to~60% and mortality from < 5% to~20%, and extends in-patient stay by an additional 7 days on average [2][3][4]. Patients who survive AL suffer long-term consequences with reduced quality of life (QoL), high rates of wound complications, permanent stoma and increased risk of cancer recurrence [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic dehiscence is a complication in colorectal surgery. A recent systematic review showed that the overall rate of dehiscence was 8.6%, the rate of dehiscence requiring re-operation was 5.4%, the post-operative mortality was 0.4%, and the overall post-operative mortality was 1.3% [7]. We report a case of complete stoma dehiscence for abscess after colorectal surgery that was treated successfully using VAC therapy.…”
mentioning
confidence: 86%